Human right to development and the state’s liability: the national damage and the role of Labor Public Prosecution - Neto, Manoel Jorge e Silva (Revista do Programa de Pós-Graduação em Direito, 2015)
This article seeks to explore the human right to development and the States’ liability as a consequence of the construction of barriers to the development of other States. Moreover, it seeks to consolidate the idea of national damage, which is a result of an act that hinders the exercise of this human right by any people. There is also an attempt to refer the relevance of the Labor Public Office to make effective the human right to development.